4x-y=9

Subtract 4x from both sides of the equation.

-y=9-4x

Multiply each term in -y=9-4x by -1

Multiply each term in -y=9-4x by -1.

(-y)⋅-1=9⋅-1+(-4x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=9⋅-1+(-4x)⋅-1

Multiply y by 1.

y=9⋅-1+(-4x)⋅-1

y=9⋅-1+(-4x)⋅-1

Simplify each term.

Multiply 9 by -1.

y=-9+(-4x)⋅-1

Multiply -1 by -4.

y=-9+4x

y=-9+4x

y=-9+4x

y=-9+4x

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-9+4(0)

Simplify -9+4(0).

Multiply 4 by 0.

y=-9+0

Add -9 and 0.

y=-9

y=-9

Use the x and y values to form the ordered pair.

(0,-9)

(0,-9)

Remove parentheses.

y=-9+4(1)

Simplify -9+4(1).

Multiply 4 by 1.

y=-9+4

Add -9 and 4.

y=-5

y=-5

Use the x and y values to form the ordered pair.

(1,-5)

(1,-5)

Remove parentheses.

y=-9+4(2)

Simplify -9+4(2).

Multiply 4 by 2.

y=-9+8

Add -9 and 8.

y=-1

y=-1

Use the x and y values to form the ordered pair.

(2,-1)

(2,-1)

These are three possible solutions to the equation.

(0,-9),(1,-5),(2,-1)

Find Three Ordered Pair Solutions 4x-y=9